Should We Monitor Space Weather Effects on Surveillance Technologies Used in Air Traffic Management?—First Results - Erik Schmölter; Jens Berdermann; Volker Wilken; David Wenzel (Space Weather, 2025)
Abstract Space weather events can disrupt satellite navigation, potentially compromising also the accuracy of real‐time flight tracking via Automatic Dependent Surveillance‐Broadcast (ADS‐B). This in turn could limit the situational awareness of pilots and reduce the efficiency of the air traffic management. This study shows these impacts of space weather for selected flight tracks during the 9 February 2024 solar flare and compares the ADS‐B reported data with solar flux and total electron content measurements. Gaps and position errors in ADS‐B reported data, which reduce the visibility of the aircraft to other participants in the airspace, correlate well with the flare peaks and corresponding ionospheric disturbances showing a clear impact. These first results are further used to discuss appropriate space weather products for the pilot briefing as well as in‐flight monitoring, since existing approaches can be extended with the ADS‐B information to provide more precise space weather predictions.